Analysis of the Effectiveness of E-Objection in Making It Easier for Officers and Taxpayers during the Covid-19 Pandemic at the Cibitung Primary Tax Service Office - Irawati; Musa Maha Sulung Sitinjak; Dwikora Harjo; Aramia Fahriah (Yayasan Ilomata, 2023)
E-Objection is one of the services of the Directorate of Taxes that can be used by taxpayers in submitting tax objection letters. E-Objection is an adoption policy that is an alternative to the previous program, namely the manual submission of objection letters. E-Objection can be accessed via E-Filling. This research is motivated by the lack of exploration of the introduction of E-Objection to taxpayers that there are still many who submit objection letters manually. Based on the data submitted by the Directorate General of Taxes (Direktorat Jenderal Pajak/DJP) and previous research in 2021 based on 2020 data, data on submitting objection letters online (E-Objectionareis still very minimal so that are problems in analyzing the effectiveness of E-Objection. Therefore, this study was conductedtoo to analyze the effectiveness of E-Objection from 2020 to 2021 at KPP Pratama Cibitung, but because the data of taxpayers who submitted objection letters by E-Objection was confidential, it was hindered from interviewing informants who had accessed E-Objection besides that because E-Objection data could not be accessed from KPP Pratama, so in this study using two research objects, namely KPP Pratama Cibitung and Kanwil DJP II. So that the purpose of this study can determine the effectiveness of E-Objection as an alternative to the previous system. Based on E-Objection data in the West Java DJP Regional Office II in 2020 there were 109 data and in 2021 there were 115 data so it could be known that there was an increase, but based on the percentage of effectiveness criteria, the percentage of e-objection effectiveness in the DJP of the West Java Regional Office II in 2020 was 8.93% and in 2021 it was 9.75% so that it can be concluded that the analysis of the effectiveness of E-Objection in KPP Pratama Cibitung during the Covid-19 pandemic (2020-2021) was ineffective.